Revitalizing Cooperatives in Medan Municipal City, Indonesia: An Alternative Concept and Approach (International Journal of Scientific Research and Management (IJSRM), 2017)
In 2012, the Indonesian government launched revitalization program towards enhancing the governance of Indonesian cooperatives. However, there are cases found to date highlighting that majority of cooperatives in Medan city are govern out of Co-operative Principles and Values (CPV). The aims of this study are:1) Finding out the contributing factors why the cooperatives are managed out of CPV, 2). Propose an alternative solution to address the causes of problems to succeed cooperatives revitalization. To achieve these purposes, we measured Stakeholders’ understanding in- how important to adapt CPV in managing co-operatives, and also measured application level of CPV that has been done during and prior to the research. To measure level of understanding, data were analyzed using Confirmatory Factor Analysis (CFA), while to measure level of CPV application, used an average value of questionnaires scale. Findings suggest CPV implementation has been misconducted in the management of cooperatives, mainly due to poor Quality of Human Resources (QHR). Accordingly, Revitalization of human resources is the key to revitalize co-operatives, by emerging and integrating CPV knowledge education as well as of leadership, competencies throughout the continuous effort of character building. The model of cooperatives revitalization is presented separately in the appendix.